Paracelsus: Historisch-kritische Ausgabe - Schnitzler, Arthur (Verlag der Österreichischen Akademie der Wissenschaften, 2021)
Historical-critical edition of Arthur Schnitzler's one-act verse drama "Paracelsus" (written 1894-1898). This edition presents a detailed preface, documenting both the genesis of the text as well as the printing history, a transcription of the genetic materials with facsimiles, a print text with a display of textual variants and a commentary.